Studi Kebijakan dalam Optimalisasi Pajak dan Retribusi Parkir dalam Mendongkrak PAD di Kota Bandung - Deni Fauzi Ramdani; Rodlial Ramdhan Tackbir Abubakar; Joni Dawud (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2021)
Parking taxes and retribution are an important part as an element of regional revenue. The existence of decentralization encourages regions to continue to make optimizations that can increase income. This article tries to explore by examining the policies and innovations carried out by the Bandung City government as an effort to increase local revenue. Parking taxes and retribution as the achievement of the expected target. This article is a policy study in regional financial management. This research uses a qualitative descriptive approach with primary and secondary data collection from informants. The result is a policy taken by the Bandung City government by carrying out the elasticity and effectiveness policy process to boost and increase revenue from taxes and parking fees